Development, validity and reliability of the 4-point likert turkish version of cognitive failures questionnaire (Annals of Medical Research, 2021)
Aim: Cognitive failures are suggested to be a transdiagnostic endophenotype that increases the vulnerability for psychiatric disorders. Broadbent’s Cognitive Failures Questionnaire (CFQ), is among the most widely used scales to assess cognitive function observed in an ecological manner. Despite its wide use in research and correlation with biological markers, CFQ is criticized for its unstable factorial structure among studies and 5-Likert structure that may lead to bias for neutral answers. Here we aimed to develop a 4-Likert Turkish version of CFQ, search its validity, reliability and factorial structure. Material and Methods: CFQ has been translated to Turkish in two steps. CFQ, Perceived Deficit Questionnaire-D (PDQ-D), Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) were applied to 272 participants (187 healthy controls, 55 patients diagnosed with depression, 30 patients diagnosed with anxiety disorder).Results: The Cronbach’s alpha coefficient of 4-Likert Turkish version of CFQ was found as 0.91. Principal component analysis extracted five factors and explained 53.7 % of total variance. CFQ scores were significantly different among groups. Both depressive and anxious groups reported higher CFQ scores compared to controls. CFQ significantly and strongly correlated with PDQ-D and showed a moderate correlation with BDI and BAI. Conclusion: 4-Likert Turkish version of CFQ is a valid and reliable tool to assess cognitive failures in non-demented groups. Our analysis revealed a five factorial structure for CFQ, however previous literature with the 5-Likert version shows different factor structures and does not indicate a dimensional stability.
Keywords: nxiety; cognitive failure; depression; validity